Preparation method and application of integrated electrode-electrolyte sheet
Through integrated electrode-electrolyte tablet preparation methods, using materials with similar structures/composition to build a transmission network of high-speed electronics and ions, solving the problem of incomplete contact in the interface in the solid sodium ion battery, and realizing efficient charge transmission and stable interface interfaces , Increase the energy density and cycle life of the battery.
Patent Information
- Application Number
- CN202411585100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
AI Technical Summary
In existing solid sodium ion batteries, the interface contact between the sodium ion solid electrolyte and the electrode is not tight, resulting in high interface resistance and poor interface stability, limiting the number of active sites for rapid transfer of sodium ions and charge transfer reactions.
Adopt an integrated electrode-electrolyte tablet preparation method. By mixing the inorganic sodium ion solid electrolytes, pore makers and conductive agents, it is closely integrated through high pressure to form an electrode and electrolyte with similar structure/composition, building high-speed electronics and building high-speed electronics and Ion conduction network.
The tight interface contact between the electrode and the electrolyte is realized, the effect of the space charging layer is reduced, the charge transmission rate and interface stability of the solid battery are improved, the interface impedance is reduced, and the energy density and cycle life of the battery is improved.
Smart Images

Figure CN119381578A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state batteries, and in particular relates to a method for preparing an integrated electrode-electrolyte sheet and its application. Background Art
[0002] The core components of solid-state sodium-ion batteries include sodium-ion positive electrode materials, sodium-ion solid electrolytes, and sodium-ion battery negative electrode materials. Among them, the sodium-ion solid electrolyte, as the core component for sodium ion transmission and electron isolation, needs to have high sodium ion conductivity, good interface contact with the electrode, high mechanical strength, and a wide electrochemical stability window. Common sodium-ion solid electrolytes currently studied mainly include oxides, sulfides, and polymers. These materials have certain advantages in improving ionic conductivity and electrochemical stability windows, but they also face challenges such as high interface resistance and poor interface stability.
[0003] High interfacial resistance is mainly caused by insufficient contact area between the solid sodium ion electrode and the solid sodium ion electrolyte. Poor interfacial contact limits the rapid transport of sodium ions and also reduces the number of active sites for charge transfer reactions. Relevant studies have attempted to improve interfacial contact by reducing electrode particle size, molten salt method, screen printing, and spark plasma sintering, but side reactions and diffusion between elements between different electrode and electrolyte materials during synthesis or charge-discharge cycles may also form new interfacial phase layers with high resistance. In addition, the close contact achieved during the preparation and sintering process may even accelerate unnecessary chemical reactions and diffusion between elements. In addition, the space charge layer formed at the heterogeneous interface between the electrode and the electrolyte due to its electrochemical potential difference may also increase the interfacial resistance. In order to minimize these unnecessary interfacial interactions, relevant studies have attempted to use surface coatings on the electrodes and add buffer layers at the electrode-electrolyte interface. Although there are some improvements in the effect, the interfacial resistance is still too high and may even increase with charge-discharge cycles. This may be mainly related to the high stress strain generated at the interface, because the large volume change of the electrode during the sodium ion insertion and extraction process is highly constrained by the solid electrolyte. Unfortunately, this problem becomes more severe for electrodes with higher loadings.
[0004] For the preparation of conventional solid-state sodium-ion batteries, the electrode sheet and the electrolyte sheet are prepared separately and independently, and the prepared electrolyte sheet is thicker, the electrode loading is lower, and the interface contact between the two is poor. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an integrated electrode-electrolyte sheet and its application, so as to overcome at least one of the above-mentioned defects in the prior art.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The method for preparing an integrated electrode-electrolyte sheet provided by the present invention comprises the following steps: S1: uniformly mixing 50-60wt% of an inorganic sodium ion solid electrolyte, 30-40wt% of a pore-forming agent, and 5-10wt% of a conductive agent to obtain a mixed powder A; S2: uniformly mixing 60-70wt% of an inorganic sodium ion solid electrolyte and 30-40wt% of a pore-forming agent to obtain a mixed powder B; S3: flattening the mixed powder A, then adding the mixed powder B to the flattened mixed powder A, flattening the mixed powder B, pressing the mixed powder A and the mixed powder B, maintaining the pressure for 10-20min, and then demolding to obtain a sheet; S4: sintering the sheet obtained in step S3 for 3-6h under an inert atmosphere to obtain an integrated electrode-electrolyte sheet.
[0008] Preferably, the chemical formula of the inorganic sodium ion solid electrolyte is Na 1+x Zr2Si x P 3-x O 12 , Na3PS4 or Na x M1[M2(CN)6] y · z H2O, Na 1+x Zr2Si x P 3-x O 12 In, x=0-3, Na x M1[M2(CN)6] y · z In H2O, x=1.8-2, y=0.8-1, z=0-4, and M1 and M2 are both transition metal elements.
[0009] Preferably, the pore former is oxalic acid dihydrate or polymethyl methacrylate.
[0010] Preferably, the conductive agent is reduced graphene or carbon nanotubes.
[0011] Preferably, in step S1 and step S2, the mixing is performed by ball milling, the ball milling speed is 400-600 rpm, the ball milling time is 6-8 h, and the mass ratio of the mixture in step S1 to the ball milling beads and the mass ratio of the mixture in step S2 to the ball milling beads is 1:8-20.
[0012] Preferably, in step S3, the mixed powder A is placed in a powder tabletting mold with an inner diameter of 10-15 mm for pressing, and the mixed powder A and mixed powder B are pressed at a pressure of 750-10000 MPa. In step S4, the sintering temperature is 170-190°C.
[0013] Preferably, the method further includes the following steps: S5: adding a polymer electrolyte and a sodium salt to an organic solvent to form a polymer electrolyte / sodium salt solution, dripping the polymer electrolyte / sodium salt solution on the upper surface of the integrated electrode-electrolyte sheet obtained in step S4, and vacuum drying at 60-80°C for 5-10 minutes, S6: taking out the integrated electrode-electrolyte sheet after vacuum drying in S5, and repeating step S5 until the pores inside the integrated electrode-electrolyte sheet are completely filled.
[0014] Preferably, the method further includes the following steps: S7: adding a polymer electrolyte and a sodium salt to an organic solvent to form a polymer electrolyte / sodium salt solution, dripping the polymer electrolyte / sodium salt solution on the upper surface of the integrated electrode-electrolyte sheet filled in step S6 until the polymer electrolyte / sodium salt solution completely covers the upper surface of the integrated electrode-electrolyte sheet filled in step S6, and vacuum drying at 60-80°C for 10-20 minutes.
[0015] Preferably, in step S5 and step S7: the polymer electrolyte is polyethylene oxide, polyacrylonitrile or polyvinylidene fluoride, the sodium salt is sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate or sodium perchlorate, the organic solvent is acetonitrile or dimethylformamide, and the molar ratio of polymer monomer to sodium ion in the polymer electrolyte / sodium salt solution is 18-20:1. The mass concentration of the polymer electrolyte / sodium salt solution in step S5 is 5-10 g / L, and the mass concentration of the polymer electrolyte / sodium salt solution in step S7 is 50-80 g / L.
[0016] The present invention also provides an application of an integrated electrode-electrolyte sheet prepared by the above-mentioned integrated electrode-electrolyte sheet preparation method in the preparation of a solid-state sodium ion battery.
[0017] The beneficial effects of the present invention are:
[0018] 1. The interface between the electrode and the electrolyte is in close contact. Both the electrode and the electrolyte come from substrate materials with similar structures / compositions, which reduces the hindrance of the space charge layer effect to ion migration.
[0019] 2. By selecting materials with similar structures / compositions as electrodes and electrolytes at the same time, and introducing conductive materials and flexible polymer electrolytes on the electrode side to construct a high-speed electron and ion conduction network, and introducing flexible polymer electrolytes on the electrolyte side to construct a high-speed ion transmission network, and combining the two tightly together through high pressure to form an integrated electrode-electrolyte sheet, the charge transfer rate of solid-state batteries can be improved, the interface impedance can be reduced, and the interface stability can be improved.
[0020] 3. Compared with the conventional electrode preparation process, the integrated electrode-electrolyte sheet prepared by the present invention avoids the use of N-methylpyrrolidone (NMP) and current collector, uses environmentally friendly raw materials, produces less environmental pollution, has a relatively simple process route, and the electrode loading capacity is higher than 60 mg cm -2 , which is conducive to achieving high energy density.
[0021] 4. By adding a conductive agent to construct a three-dimensional current collection network inside the electrode, faster electron transmission can be achieved. The porosity inside the prepared integrated electrode-electrolyte sheet can be as high as 30%-50%. After composite filling with polymer electrolyte / sodium salt, the integrated electrode-electrolyte sheet can have high mechanical strength, ionic conductivity and electronic conductivity.
[0022] 5. The thickness of the integrated electrode-electrolyte sheet is controllable, and a thinner integrated electrode-electrolyte sheet is conducive to achieving faster ion transport.
[0023] 6. By combining flexible polymers with inorganic fillers, the ionic conductivity and mechanical strength of electrodes and electrolytes are improved, thereby alleviating problems such as poor interface contact caused by electrode volume expansion during battery charging and discharging.
[0024] 7. The prepared solid-state sodium-ion battery has close interface contact, low interface impedance, stable overall battery structure, and high safety performance. The battery energy density is greater than 100Wh / kg, and the cycle life is greater than 100 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional SEM image of the porous integrated electrode-electrolyte sheet prepared in Example 1 of the present invention.
[0026] Figure 2 This is a cross-sectional SEM image of the composite integrated electrode-electrolyte sheet prepared in Example 1 of the present invention.
[0027] Figure 3 This is an AC impedance test graph of the composite integrated electrode-electrolyte sheet prepared in Example 1 of the present invention.
[0028] Figure 4 This is a graph showing the capacity change of the integrated all-solid-state sodium-ion battery assembled in Example 1 of the present invention after 100 cycles at 1C.
[0029] Figure 5 This is a capacity change diagram of the integrated all-solid-state sodium ion battery assembled in Example 2 of the present invention after 100 cycles at 1C. DETAILED DESCRIPTION
[0030] The present invention will now be further described with reference to the accompanying drawings and specific implementation methods.
[0031] Embodiment 1:
[0032] The method for preparing the integrated electrode-electrolyte sheet provided in this embodiment comprises the following steps:
[0033] S1: 60wt% Na 1.8 Fe[Fe(CN)6] 0.96 · 2.26 H2O, 30wt% of oxalic acid dihydrate, and 10wt% of carbon nanotubes were ball-milled and mixed, the mass ratio of the mixture to the ball milling beads was 1:10, the ball milling speed was 600rpm, the ball milling time was 6h, and after ball milling, a mixed powder A with uniform distribution of the three was obtained. The purpose of this step is to utilize the high ionic conductivity and certain redox characteristics of the inorganic electrolyte, and mix it with a conductive agent with high electronic conductivity as the base material of the sodium ion positive electrode sheet. And the porous network inside the sodium ion electrolyte sheet is constructed by adding oxalic acid dihydrate to facilitate the subsequent introduction of flexible polymers.
[0034] S2: 60wt% Na 1.7 Mn[Fe(CN)6] 0.7 · 1.04 H2O and 40wt% of dihydrated oxalic acid were mixed by ball milling, the mass ratio of the mixture to the ball milling beads was 1:10, the ball milling speed was 600rpm, the ball milling time was 6h, and after ball milling, a mixed powder B in which the two were evenly distributed was obtained. The purpose of this step is to achieve the construction of a porous network inside the sodium ion electrolyte sheet by adding a pore-forming agent, so as to facilitate the subsequent introduction of a flexible polymer.
[0035] S3: Weigh 1g of mixed powder A, put it into a powder tableting mold with an inner diameter of 10mm, and spin it flat. Then weigh 0.1g of mixed powder B and add it to the flattened mixed powder A, and spin the mixed powder B flat. After spinning flat, use a pressure of 750MPa to press the mixed powder A and mixed powder B. Maintain the pressure for 10min and then demold to obtain a sheet.
[0036] S4: placing the sheet obtained in step S3 in a tubular furnace and sintering it for 6 hours in a nitrogen atmosphere at a sintering temperature of 180° C. to obtain a porous integrated electrode-electrolyte sheet. Figure 1 The cross-sectional SEM image of the porous integrated electrode-electrolyte sheet prepared in this embodiment shows that the pores are evenly distributed, and the electrode and electrolyte interface are in close contact, with the electrolyte layer thickness being only about 50 μm. In this step, since the pore former inside the integrated electrode-electrolyte sheet is removed, the interface contact between the electrode and the electrolyte sheet is closer after sintering.
[0037] S5: Weigh 0.4 g of polyethylene oxide (PEO) and 0.145 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and add them to 60 mL of acetonitrile solution to prepare a polymer electrolyte / sodium salt solution (PEO / NaTFSI solution) with a mass concentration of 9 g / L. Use a dropper to drop 3 mL of the prepared polymer electrolyte / sodium salt solution with a concentration of 9 g / L onto the upper surface of the porous integrated electrode-electrolyte sheet obtained in step S4, and vacuum dry at 60° C. for 10 min.
[0038] S6: After taking out the porous integrated electrode-electrolyte sheet after vacuum drying in S5, repeat step S5 until the pores inside the porous integrated electrode-electrolyte sheet are completely filled. The purpose of steps S5 and S6 is to introduce the flexible polymer into the inorganic sodium ion solid electrolyte to improve the ionic conductivity and mechanical strength of the integrated electrode-electrolyte sheet.
[0039] S7: Weigh 0.4g of polyethylene oxide (PEO) and 0.145g of sodium bis(trifluoromethylsulfonyl imide) (NaTFSI) and add them to 10mL of acetonitrile solution to prepare a polymer electrolyte / sodium salt solution (PEO / NaTFSI solution) with a mass concentration of 50g / L. Use a dropper to drop 3mL of the prepared polymer electrolyte / sodium salt solution with a mass concentration of 50g / L on the upper surface of the integrated electrode-electrolyte sheet filled in step S6 until the polymer electrolyte / sodium salt solution can just completely cover the upper surface of the integrated electrode-electrolyte sheet filled in step S6. Vacuum dry at 60°C for 20min to obtain a composite integrated electrode-electrolyte sheet. The purpose of this step is to avoid direct contact between sodium metal and inorganic sodium ion solid electrolyte, which leads to the reduction of some metal ions, and at the same time improve the interface contact between the two. Figure 2 It can be seen that the pores of the composite integrated electrode-electrolyte sheet are completely filled. Figure 3 As shown, according to the formula σ=L / (R·S), it can be calculated that the room temperature ionic conductivity of the composite integrated electrode-electrolyte sheet obtained in this embodiment is 0.22 mS / cm.
[0040] This embodiment also provides an application of the integrated electrode-electrolyte sheet prepared by the above-mentioned integrated electrode-electrolyte sheet preparation method in the preparation of a solid-state sodium ion battery. Specifically, the obtained composite integrated electrode-electrolyte sheet is used as the positive electrode and electrolyte, sodium metal is used as the negative electrode, the sodium metal is punched into a size of 10 mm, and the two are assembled to obtain an integrated all-solid-state sodium ion battery. The loading capacity of the integrated sheet is 62 mg cm -2 The thickness is about 600μm. The assembled all-solid-state sodium ion battery was tested using the Xinwei test system with a test voltage range of 2-4V and a test rate of 1C. Figure 4As shown, the integrated all-solid-state sodium ion battery assembled in this embodiment has a capacity retention rate of 85.8% after 100 cycles at 1C, and an energy density of about 101Wh / kg.
[0041] Embodiment 2:
[0042] The method for preparing the integrated electrode-electrolyte sheet provided in this embodiment comprises the following steps:
[0043] S1: 60wt% Na3Zr2Si2PO 12 , 30wt% of oxalic acid dihydrate, and 10wt% of reduced graphene are ball-milled and mixed, the mass ratio of the mixture to the ball milling beads is 1:10, the ball milling speed is 600rpm, and the ball milling time is 6h. After ball milling, a mixed powder A in which the three are evenly distributed is obtained.
[0044] S2: 60wt% Na3Zr2Si2PO 12 , and 40wt% of oxalic acid dihydrate were ball-milled, the mass ratio of the mixture to the ball milling beads was 1:10, the ball milling speed was 600rpm, the ball milling time was 6h, and after ball milling, a mixed powder B in which the two were evenly distributed was obtained.
[0045] S3: Weigh 1.5g of mixed powder A, put it into a powder tableting mold with an inner diameter of 10mm, and flatten it. Then weigh 0.2g of mixed powder B and add it to the flattened mixed powder A, and flatten the mixed powder B. After flattening, press the mixed powder A and mixed powder B with a pressure of 1000MPa, maintain the pressure for 20min, and then demold to obtain a sheet.
[0046] S4: Place the sheet obtained in step S3 in a tube furnace and sinter for 4 hours under a nitrogen atmosphere at a sintering temperature of 180°C.
[0047] A porous integrated electrode-electrolyte sheet is obtained.
[0048] S5: Weigh 0.4 g of polyvinylidene fluoride (PVDF) and 0.145 g of sodium bis(trifluoromethylsulfonyl imide) (NaTFSI) and add them to 60 mL of acetonitrile solution to prepare a polymer electrolyte / sodium salt solution (PVDF / NaTFSI solution) with a mass concentration of 9 g / L. Use a dropper to drop 2 mL of the prepared polymer electrolyte / sodium salt solution with a concentration of 9 g / L onto the upper surface of the porous integrated electrode-electrolyte sheet obtained in step S4, and vacuum dry at 60° C. for 10 min.
[0049] S6: After taking out the porous integrated electrode-electrolyte sheet after vacuum drying in S5, repeat step S5 until the pores inside the porous integrated electrode-electrolyte sheet are completely filled.
[0050] S7: Weigh 0.4 g of polyvinylidene fluoride (PVDF) and 0.145 g of sodium bis(trifluoromethylsulfonyl imide) (NaTFSI) and add them to 10 mL of acetonitrile solution to prepare a polymer electrolyte / sodium salt solution (PVDF / NaTFSI solution) with a mass concentration of 50 g / L. Use a dropper to drop 2 mL of the prepared polymer electrolyte / sodium salt solution with a mass concentration of 50 g / L on the upper surface of the integrated electrode-electrolyte sheet filled in step S6 until the polymer electrolyte / sodium salt solution can just completely cover the upper surface of the integrated electrode-electrolyte sheet filled in step S6. Vacuum dry at 60° C. for 20 min to obtain a composite integrated electrode-electrolyte sheet.
[0051] The obtained composite integrated electrode-electrolyte sheet was used as the positive electrode and electrolyte, and sodium metal was used as the negative electrode. The sodium metal was punched into a size of 10 mm, and the two were assembled to obtain an integrated all-solid-state sodium ion battery. The loading capacity of the integrated sheet was 86 mg cm -2 The thickness is about 800μm. The assembled all-solid-state sodium ion battery was tested using the Xinwei test system with a test voltage range of 2-4.6V and a test rate of 1C. Figure 5 As shown, the integrated all-solid-state sodium ion battery assembled in this embodiment has a capacity retention rate of 90.7% after 100 cycles at 1C, and an energy density of about 110Wh / kg.
[0052] The present invention selects materials with similar structures / compositions as electrodes and electrolytes at the same time, introduces conductive materials and flexible polymer electrolytes on the electrode side to construct a high-speed electron and ion conduction network, introduces flexible polymer electrolytes on the electrolyte side to construct a high-speed ion transmission network, and tightly combines the two together in the form of high pressure to form an integrated electrode-electrolyte sheet. The charge transfer rate of the solid-state battery can be improved, the interface impedance can be reduced, and the interface stability can be improved. The solid-state battery prepared by the present invention has high energy density and power density, good cycle stability and high safety and reliability. Rapid charge transfer can be achieved by constructing a porous conductive network inside the high-load electrode-electrolyte, and the polymer electrolyte is introduced to compound with the electrode-electrolyte to improve the sodium ion conductivity and mechanical strength of the integrated electrode-electrolyte sheet.
[0053] Compared with conventional electrode preparation processes, the integrated electrode-electrolyte sheet prepared by the present invention avoids the use of PVDF, NMP and current collectors, uses environmentally friendly raw materials, generates little environmental pollution, has a relatively simple process route, and has an electrode loading capacity of more than 60 mg cm -2 , which is conducive to achieving high energy density.
[0054] The present invention constructs a three-dimensional current collection network inside the electrode by adding a conductive agent, which can achieve faster electron transmission. The porosity inside the prepared integrated electrode-electrolyte sheet can be as high as 30%-50%. After composite filling with polymer electrolyte / sodium salt, the integrated electrode-electrolyte sheet can have high mechanical strength, ionic conductivity and electronic conductivity.
[0055] The thickness of the integrated electrode-electrolyte sheet in the present invention is controllable, and a thinner integrated electrode-electrolyte sheet is conducive to achieving faster ion transport. In addition, the interface contact between the electrode and the electrolyte is close, and the electrode and the electrolyte are both made from substrate materials with similar structures / compositions, which reduces the obstruction of the space charge layer effect on ion migration.
[0056] The present invention improves the ionic conductivity and mechanical strength of the electrode and the electrolyte by compounding the flexible polymer with the inorganic filler, thereby alleviating problems such as poor interface contact caused by the volume expansion of the electrode during the battery charging and discharging process.
[0057] The solid-state sodium ion battery prepared by the present invention has close interface contact, low interface impedance, stable overall battery structure, high safety performance, battery energy density greater than 100Wh / kg, and cycle life greater than 100 times.
[0058] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an integrated electrode-electrolyte sheet, characterized in that: The following steps are involved: S1: 50-60wt% of an inorganic sodium ion solid electrolyte, 30-40wt% of a pore-forming agent, and 5-10wt% of a conductive agent are uniformly mixed to obtain a mixed powder A; S2: 60-70 wt% of an inorganic sodium ion solid electrolyte and 30-40 wt% of a pore former are uniformly mixed to obtain a mixed powder B; S3: Screw the mixed powder A flat, then add the mixed powder B onto the spun-flat mixed powder A, and screw the mixed powder B flat, press the mixed powder A and the mixed powder B, maintain the pressure for 10-20 minutes, and then demold to obtain a sheet; S4: Sintering the sheet obtained in step S3 for 3-6 hours under an inert atmosphere to obtain an integrated electrode-electrolyte sheet.
2. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: The chemical formula of the inorganic sodium ion solid electrolyte is Na 1+x Zr2Si x P 3-x O 12 , Na3PS4 or Na x M1[M2(CN)6] y · z H2O; Na 1+x Zr2Si x P 3-x O 12 where x = 0 - 3; Na x M1[M2(CN)6] y · z In H2O, x=1.8-2, y=0.8-1, z=0-4, and M1 and M2 are both transition metal elements.
3. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: The pore-forming agent is oxalic acid dihydrate or polymethyl methacrylate.
4. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: The conductive agent is reduced graphene or carbon nanotubes.
5. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: In step S1 and step S2, the mixing is performed by ball milling, the ball milling speed is 400-600 rpm, and the ball milling time is 6-8 h; The mass ratio of the mixture in step S1 to the ball milling beads and the mass ratio of the mixture in step S2 to the ball milling beads are both 1:8-20.
6. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: In step S3, the mixed powder A is placed in a powder tabletting mold with an inner diameter of 10-15 mm for pressing, and the mixed powder A and the mixed powder B are pressed at a pressure of 750-10000 MPa; In step S4, the sintering temperature is 170-190°C.
7. The method for preparing an integrated electrode-electrolyte sheet according to claim 1, characterized in that: The following steps are also included: S5: adding a polymer electrolyte and a sodium salt to an organic solvent to form a polymer electrolyte / sodium salt solution, dripping the polymer electrolyte / sodium salt solution onto the upper surface of the integrated electrode-electrolyte sheet obtained in step S4, and vacuum drying at 60-80° C. for 5-10 min; S6: After taking out the integrated electrode-electrolyte sheet after vacuum drying in S5, repeat step S5 until the pores inside the integrated electrode-electrolyte sheet are completely filled.
8. The method for preparing an integrated electrode-electrolyte sheet according to claim 7, characterized in that: The following steps are also included: S7: Add a polymer electrolyte and a sodium salt to an organic solvent to form a polymer electrolyte / sodium salt solution, and drop the polymer electrolyte / sodium salt solution on the upper surface of the integrated electrode-electrolyte sheet filled in step S6 until the polymer electrolyte / sodium salt solution completely covers the upper surface of the integrated electrode-electrolyte sheet filled in step S6, and vacuum dry at 60-80°C for 10-20min.
9. The method for preparing an integrated electrode-electrolyte sheet according to claim 8, characterized in that: In step S5 and step S7: The polymer electrolyte is polyethylene oxide, polyacrylonitrile or polyvinylidene fluoride; The sodium salt is sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate or sodium perchlorate; The organic solvent is acetonitrile or dimethylformamide; In the polymer electrolyte / sodium salt solution, the molar ratio of polymer monomer to sodium ion is 18-20:1; The mass concentration of the polymer electrolyte / sodium salt solution in step S5 is 5-10 g / L; The mass concentration of the polymer electrolyte / sodium salt solution in step S7 is 50-80 g / L.
10. Use of the integrated electrode-electrolyte sheet prepared by the method for preparing an integrated electrode-electrolyte sheet according to any one of claims 1 to 9 in preparing a solid-state sodium ion battery.